Zootopia [videorecording (Blu-Ray + DVD)] - Bush, Jared, 1974-; Johnston, Phil (Disney Blu-ray., 2016)
Zootopia is a city like no other. Comprising habitat neighborhoods like ritzy Sahara Square and frigid Tundratown, it's a melting pot where animals from every environment live together. But when optimistic Officer Judy Hopps arrives, she discovers that being the first bunny on a police force of big, tough animals isn't so easy. Determined to prove herself, she jumps at the opportunity to crack a case, even if it means partnering with a fast-talking, scam-artist fox, Nick Wilde.